Análise Swot dos relatórios de avaliação interna: um diagnóstico institucional do IFPB - Fontes Filho, José de Arimatéa (2023)
This research provides an overview of the study's theme, which focuses on institutional selfassessment processes conducted by the Federal Institute of Education of Paraíba (IFPB), a higher education institution comprising multiple units throughout the state. These institutions are subject to specific regulations governing the National Higher Education Assessment System (SINAES), which aims to consolidate the national evaluation process of Higher Education Institutions (HEIs), their undergraduate courses, and student academic performance. Within this context, IFPB carries out institutional self-assessment through the Commission for Self- Assessment (CPA), responsible for collecting and analyzing information from faculty, students, administrative staff, and the community surrounding the institution. The purpose of the selfassessment process is to diagnose the conditions under which IFPB operates in higher education, and it is essential for improving the quality of undergraduate and postgraduate courses, research, extension activities, and community engagement. Considering the potential personal, professional, and institutional obstacles related to self-assessment, this research intends to approach evaluation holistically and view it as a fundamental exercise for institutional quality improvement, aiming for continuous development. The self-assessment reports produced by the CPA are relevant for planning and implementing actions that aim to continually enhance the conditions for offering courses and services at IFPB. In this regard, the research focuses on analyzing these reports, seeking to understand their content and presentation methods to provide better visibility and comprehension. With the overall objective of conducting a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) of IFPB's selfassessment processes, the research aims to compile insights from the reports and generate suggestions for the organization under study.